Influence of economical variables on a supercritical biodiesel production process - Marchetti, Jorge Mario (2013)
Biodiesel has becoming more and more relevant in today’s society and economy due to its environmental advantages such as biodegradability, lower CO and CO2 emissions as well as less particulate pollutants. In this work the study of market and economic variables is presented and their effects compared when biodiesel is being produced using a supercritical technology. The production process is based on a supercritical technology with no catalyst and no co-solvent. Price for the raw materials, such as price for the alcohol as well as the oil has been studied. Also, selling price for biodiesel as well as glycerin has been analyzed and compared with prices from other biodiesel production technologies. Economic decisions such as percentage of failure in the production process, investment in research and development, and advertisement have been evaluated; also it has been considered the influence of the tax incentives on the global economy of the production process. Small variations on some of the major market variables would produce significant effects over the global economy of the plant, making it non profitable in some cases.